Phthalate Acid Esters in Soil, Plastic Shed Film, and Ginseng Tissues of Different Ages From Farmland: Concentration, Distribution, and Risk Assessment - Lu, Yu-Shun; Xu, Yan-Yang; Zhang, Yan-Ting; Liu, Zheng-Bo; Li, Wei; Sun, Yin-Shi (Frontiers in Environmental Science, 2022)
Plastic shed film used in ginseng cultivation could increase phthalate acid esters (PAEs) residues in ginseng and its planting soil. This study recorded the situation of 19 PAEs in ginseng, soil and plastic shed film samples from eight ginseng cultivation bases in Jilin Province, China. The results showed that 6 PAEs are omnipresent contaminants in ginseng cultivation bases. The Σ19 PAEs residue ranged from 0.69 to 3.30 mg•kg-1 in the soil and from 32.40 to 96.20 mg•kg-1 in the plastic shed film. Plastic shed film is possibly one source of PAEs in ginseng bases. In addition, PAEs concentrations in different ginseng tissues (roots, stems and leaves) showed significant differences (P < 0.05). The residues of Σ19 PAEs in ginseng roots and stems were 0.71~2.10 mg•kg-1 (dry weight (dw)) and 1.56~4.69 mg•kg-1 (dw), respectively, lower than the 2.37~6.82 mg•kg-1 (dw) in leaves (P < 0.05). PAEs more readily accumulated in ginseng leaves than in roots and stems. Cultivation age also influenced PAEs accumulation in ginseng. PAEs residues in three-year-old ginseng plants were higher than those in annual and biennial ginseng (P < 0.05). The noncancer and carcinogenic risk assessments of the target PAEs in ginseng indicated acceptable levels for adult intake. This study provides data for understanding the concentration, distribution and potential risk of PAEs in ginseng and its cultivated soil.